Limitations on point care APTT for monitoring of unfractionated heparin in intensive care patients. Issue 181 (September 2019) - Arachchillage, Deepa R.J.; Vipond, Lisa; Laffan, Mike
Highlights: There are limitations in use of APTT for monitoring of unfractionated heparin (UFH). APTT was checked on Coagucheck, ACL TOP500 analyser and compared with heparin anti-Xa. Neither POCT nor laboratory APTT is suitable for monitoring unfractionated heparin.